Analysis of Volatile Compounds from Different Parts of Citrus grandis (L.) Osbeck Flowers by Headspace Solid-Phase Microextraction-Gas Chromatography-Mass Spectrometry. Issue 4 (4th July 2017) - Huang, Hsing-Hsuan; Lin, Li-Yun; Chiang, Hsiu-Mei; Lay, Shin-Jong; Wu, Chin-Sheng; Chen, Hsin-Chun
Abstract: The volatile compounds obtained from different parts of fresh buntan shaddock flowers ( Citrus grandis (L.) Osbeck grown in Taiwan) were analysed by solid phase microextraction (SPME) coupled with gas chromatography (GC) and gas chromatography/mass spectrometry (GC-MS). A total of 39 compounds were present in different parts of the buntan shaddock flowers, and 46 identified in the essential oils. The major volatile compounds present in the whole flowers, flower buds, petals, filaments, and anthers plus pollens were linalool, limonene, β-Pinene and β-Ocimene. The receptacles, ovaries, columns and essential oils were primarily composed of β-Pinene, limonene and β-Ocimene. Both geraniol and nerol were identified in the whole flowers, and in the flower oils, providing the source of the fragrance. Increased levels of terpene esters were identified in the flower oils compared with the other samples.